FAKTOR-FAKTOR PENGARUH KEBERHASILAN DALAM PENDIDIKAN AGAMA UNTUK ANAK - Hadi Muhtarom; Ahmad Miftahun Ni’am (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2018)
This research aims to find out: (1) What is the factors influence the success ofreligious education for children? (2) How to educate good religious educationfor children? This research using qualitative methods while the type of researchused is library research. The discussion is based on literature review and severalwritings that have relevance to the object of study under research. Based on theresults of research that examined that there are four factors that can influencethe success of religious education for children, that is: parents, teachers, friendsand also active in learning. If the four factors are good then it is certain thatthe educated children will be a faith. Hope in the future is by together especiallyfrom parents and teachers in making children of this age active in learning andalso not wrong in choosing friends and socializing, because that will make futuregenerations not only good enough on technology, but also good on religion